Idiopathic Scrotal Calcinosis: A Case Report and Review of Postoperative Outcomes - Mathew Yamoah Kyei; Robert Djagbletey; Afua Darkwa Abrahams; James Edward Mensah (Case Reports in Urology, 2020)
Idiopathic scrotal calcinosis is a rare condition, characterized by the idiopathic deposition of calcium in the scrotal dermis leading to the formation of a single nodule or multiple nodules of different sizes. Surgical excision of the nodules reduces symptoms and improves cosmesis. We present a case of idiopathic scrotal calcinosis that had an en bloc excision of scrotal skin nodules and primary closure of the scrotal skin. Handling each hemiscrotum as a separate entity and preserving the median raphe with its uninvolved skin improved the cosmesis. Reported outcomes of surgery were satisfactory with no postoperative complications. At 30 months of follow-up, the residual scrotal skin had regained its laxity and the scrotum its normal configuration. There is the risk of recurrence of the calcific nodules post excision, but these may be smaller in size and with regained scrotal configuration that could be amenable to excision with further preservation of the native scrotal skin.